2003
DOI: 10.1292/jvms.65.1041
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatitis in a Piglet Experimentally Inoculated with Tissue Homogenates from Pigs with Postweaning Multisystemic Wasting Syndrome

Abstract: ABSTRACT. Five 2 day-old colostrum-deprived piglets were inoculated with tissue homogenates from pigs with postweaning multisystemic wasting syndrome. One of the five piglets developed icterus and died 23 days post-inoculation. Histologic examination revealed acute hepatitis. Porcine circovirus type 2 (PCV-2) antigen and nucleic acid were detected in hepatocytes and phagocytic cells. Ultrastructurally, hepatocytes and phagocytic cells had large numbers of cytoplasmic inclusions, which were composed of electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…PCV2 immunolabelling in the apoptotic hepatocytes has been already reported by Rosell et al [20] and Hirai et al [8]. PCV2 antigens were also found in the degenerated cells which were phagocytosed by histocytes or multinuclear giant cells in the nodules, being analogous to "paratyphoid" nodules in one case.…”
supporting
confidence: 76%
“…PCV2 immunolabelling in the apoptotic hepatocytes has been already reported by Rosell et al [20] and Hirai et al [8]. PCV2 antigens were also found in the degenerated cells which were phagocytosed by histocytes or multinuclear giant cells in the nodules, being analogous to "paratyphoid" nodules in one case.…”
supporting
confidence: 76%
“…During fetal life, cardiomyocytes, hepatocytes and macrophages were main target cells of PCV2 [12]. In our previous study, we reproduced lymphadenitis and hepatitis in a piglet experimentally inoculated with tissue homogenates from pigs with PMWS [5]. The aim of this study was to confirm if PCV2 can infect primary porcine hepatocyte cultures as observed in the liver of PMWSaffected pigs.…”
mentioning
confidence: 93%
“…In many cases of PMWS, lymphadenitis and hepatitis are the commonly observed lesions. Since hepatic necrosis and/or apoptosis have been detected in the hepatic lesions of PMWS [4,5,7,9,10], hepatocytes also seem to be a target cell for PCV2 infection [5,10]. During fetal life, cardiomyocytes, hepatocytes and macrophages were main target cells of PCV2 [12].…”
mentioning
confidence: 99%
See 2 more Smart Citations